Pengaruh Video Animasi Terhadap Keterampilan Menyimak Teks Narasi Peserta Didik Kelas III SD Negeri 8 Pangkalanbaru - chery muntaza; Iful Rahmawati Mega; Yorenza Meifinda (STKIP Subang, 2025)
Third-grade students at SD Negeri 8 Pangkalanbaru will be tested on their listening skills to see how they cope when exposed to animated video media. The basis of this study is the observation that students continue to struggle with listening, especially when it comes to understanding and repeating story information. The lack of engaging and participatory educational materials is the main cause. The researchers in this study used a single-group pretest-posttest design as their experimental approach. Each of the 23 third-grade students served as a representative sample. A written test consisting of essay questions addressing five markers of listening skills was used as the instrument. The average score of 51.8 was shown on the pretest, and increased to 81 on the posttest. The use of animated video media had a substantial impact on students' listening skills, as indicated by the paired-sample t-test significance value of 0.000 < 0.05 and the normality test confirmation that the data were normally distributed.The results of this study demonstrate that the animated video Nussa and Rara effectively captured students’ attention through engaging visual and audio elements. It positively influenced their listening skills by helping them stay focused and better understand the story content. This study recommends the use of animated videos as an alternative and interactive learning medium to improve the quality of instruction, particularly in developing listening skills.